PERANCANGAN VIDEO PROMOSI PUSAT KEGIATAN BELAJAR MASYARAKAT SUKA MAJU SEJAHTERA MELALUI MEDIA SOSIAL - SOPHIA NABILA PUTERI, Dra. Zubaidah, M.Sn., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Community Learning Center is a social institution in educational field. One of community learning center in Padang is Suka Maju Sejahtera Community Learning Center, it held Equality Education Program Packet A, B, and C that is equal with Elementary School/Junior High School/and Senior High School. This Community Learning Center just move to Tepian Danau Cimpago. The impact of this movement is registrant decreased. Community also have less respond in this Equality Education. So, it is necessary to make a promotion through audio visual media which can make community interested and convinced, especially for droput people. The right promotion media is promotion video through social media.The Suka Maju Sejahtera Community Learning Center promotion video concept is cinematic video. This concept is choosen because it will be able to attract people emotion to animate that video. So people will be currious about Equality Education Program Packet A, B, and C that is held by Suka Maju Sejahtera Community Learning Center.The designing method used SWOT analysis aproach to find strength, weakness, oppurtunity, and threat in Suka Maju Sejahtera Community Learning Center promotion. Creative program used is AISAS (Attention, Interest, Search, Action, Share). AISAS is used because the people habit nowadays can not be separated with internet. The Suka Maju Sejahtera Community Learning Center promotion video designing was aplicated in promotion video main media through. Supporting media are poster, sticker, shirt, pin, brochure, clock, name card, and banner. This Suka Maju Sejahtera Community Learning Center Video Promotion through social media is expected to make Sumatra Barat community respond increase to continue their education.Keywords: Promotion Video, Suka Maju Sejahtera Community Learning Center, Social Media